Exploring Art and Design Students’ Satisfaction with Folk Art Workshops: A Case Study from Neijiang, China - Chen, Xiaoping (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study investigates the effects of six experiential factors, perceived communication, perceived trust, service, product, social value, and emotional value, on student satisfaction in folk art sales workshops, and examines changes following an educational intervention. Research design, data and methodology: A two-stage quantitative design was applied. First, a survey was distributed to 110 art and design students. Instrument validity was assessed using the Item-Objective Congruence (IOC) index, and a pilot test (n=30) confirmed reliability. Multiple linear regression analysis was conducted to determine the influence of the six independent variables on student satisfaction. Subsequently, a workshop-based intervention spanning eight weeks was implemented with 30 students to enhance experiential dimensions. Paired-sample t-tests were then used to evaluate pre- and post-intervention changes. Results: Regression results indicated that perceived communication (β=0.345), perceived trust (β=0.293), service (β=0.191), product (β=-0.136), and emotional value (β=0.197) significantly influenced satisfaction (R²=0.82), while social value had no significant effect (β=0.081). Paired-sample t-tests revealed statistically significant improvements in all satisfaction dimensions, including overall student satisfaction, from pre- to post-intervention. Conclusions: This study offers practical insights for enhancing student satisfaction in folk art education by identifying key experiential factors. It also provides a theoretical foundation for improving workshop design and fostering more engaging, value-driven learning experiences in art and design education.